English in Tanzania: A linguistic cultural perspective - Bwenge, Charles (International Journal of Language, Translation and Intercultural Communication, 2012)
Talking about ‘English in Tanzania’ or what Schneider (2007) has in general categorized as postcolonial English for that matter instantaneously evokes notions pertaining to language contact as well as the fi eld of contact linguistics. It was the British colonization of East African territories in the fi rst half of the 20th century that brought English into the region and consequently set off the contact process with indigenous local languages that would subsequently shape and defi ne the dynamics of linguistic culture as still observed today. Of particular interest is the contact and subsequent coexistence between English and Swahili especially in Tanzania. There is no any country in sub-Saharan Africa other than Tanzania that provides a perfect illustration of the dynamics of language contact in the 20th century and beyond between a European language and an indigenous African language in the African setting – to the extent that a story of ‘English in Tanzania’ would blatantly appear incomplete without bringing in a story of ‘Swahili in Tanzania’ and vice versa. This is exactly what this paper has assigned itself to do – examining a linguistic culture that has evolved in a particular time and space with English and Swahili occupying the center. Nevertheless, the literature on the topic abounds; only that its linguistic cultural dimension has not been privileged enough. Linguistic culture encompasses dynamics related to language contact phenomena such as lexical and grammatical borrowings, code-mixing, bilingualism, language shift, development of pidgins and creoles, attitudes toward languages, linguistic stereotypes and prejudices, and the like. Contact linguistics as an analytical tool pertaining to the structural aspects of bilingual language production is not marginalized in linguistic cultural approach but rather it is highlighted in order to provide concrete evidence on the cultural dimension. In this regard, ‘English in Tanzania’ is explored by contextualizing it within the parameters of the dynamics of Tanzanian linguistic cultural landscape. Specifi cally the paper outlines the dynamics of Tanzanian linguistic culture evolving around the English language, of course, alongside Swahili in terms of distinct political periods between the British colonial era and today’s era of globalization; second, it concentrates on actual language use and related public discourse as observed in public space; third, it demonstrates communicative creativity arising from the coexistence between English and Swahili and, fi nally, it concludes with recapitulation regarding the signifi cance of linguistic cultural approach to sociolinguistics explorations.